2019
DOI: 10.2166/wcc.2019.118
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of unmet water demand under climate change scenarios in the Gualí River Basin, Colombia, through the implementation of Hydro-BID and WEAP hydrological modeling tools

Abstract: Climate change can affect hydrological services in Andean basins, so a possible reduction in water supply can lead to not meeting the needs of different users, which has become a real challenge for decision-makers with regards to water management. This paper presents the results obtained from hydrological modeling exercises in the Gualí River Basin (Colombia) by combining the Hydro-BID modeling tool, which consists of an analytical hydrology database for Latin America and the Caribbean that provides a great ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Changes in land use can impact runoff and therefore the ows in a watershed. Hydro-BID, through the Customized Parameterization Tool, allows data on land use to be entered in order to parameterize the different key variables established in the software and thus calculate daily runoff (Mena et al, 2019). Data on soil texture characteristics were used after being extracted from the global database of soils from the Food and Agriculture Organization of the United Nations (FAO).…”
Section: Hydro-bid Parameterizationmentioning
confidence: 99%
“…Changes in land use can impact runoff and therefore the ows in a watershed. Hydro-BID, through the Customized Parameterization Tool, allows data on land use to be entered in order to parameterize the different key variables established in the software and thus calculate daily runoff (Mena et al, 2019). Data on soil texture characteristics were used after being extracted from the global database of soils from the Food and Agriculture Organization of the United Nations (FAO).…”
Section: Hydro-bid Parameterizationmentioning
confidence: 99%
“…In this one, HydroBID was employed as a tool that enabled fundamental hydrological modeling, which was subsequently used in other models such as WEAP. For this purpose, rainfall stations around the study basin were utilized [28]. Most of them focused on climate change scenarios analysis, but none of them explored the merit of the precipitation pattern utilizing satellite-based products.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the water unmet demand would be increasing by 2060s to 51.5% where this shortage would be more severe in irrigation among the others. Mena et al [12] studied the potential impacts of climate changes on unsatisfied demand for water in the Guila river basin in Colombia over the period 2011-2100 using the Hydro-BID modeling tool along with the WEAP. They found that the studied climate change affecting the hydrological services in Andean basins, so the reduction in the water supply can lead to unmeet water for different users.…”
Section: Introductionmentioning
confidence: 99%